Mid‐term outcomes after AdVanceXP male sling implantation. (19th March 2016) - Kretschmer, Alexander; Grabbert, Markus; Sommer, Anne; Stief, Christian G.; Bauer, Ricarda M.
Abstract : Objective: To describe efficacy and safety of the AdVanceXP (Boston Scientific, Marlborough, MA, USA) retrourethral transobturator male sling after a mean follow‐up of almost 3 years. Patients and Methods: A total of 41 patients underwent AdVanceXP implantation between July 2010 and March 2012 by a single surgeon. Patients were prospectively evaluated at baseline, after a mean follow‐up of 12months and after an individual maximum follow‐up. Efficacy was evaluated by daily pad usage, 24‐h pad testing, and validated questionnaires (International Consultation on Incontinence questionnaire [ICIQ]). Patient satisfaction was determined using the Patient's Global Impression of Improvement score; quality of life was evaluated using the International Quality of Life (IQOL) score. Patients needing 0 or 1 safety pad with a daily urine loss <8 g were classified as cured. To assess the changes in outcome over time, a Wilcoxon signed‐rank test was used. A P value <0.05 was taken to indicate statistical significance. Results: The mean ±sd follow‐up was 33.1 ± 8.1 months. A total of four patients (9.8%) were lost to follow‐up. At follow‐up, 56.1% of patients used 0 or 1 dry safety pad, 17.1% used 1 pad, and 17.1% used 2 pads. Mean pad use was 0.6 pads per day ( P < 0.001 vs baseline) with a mean urine loss of 14 g per day. After nearly 3 years, 46.3% of the patients could be classified as cured and 29.3% could be classified as improved. When comparing respective outcomes after 1 and 3 years, no significant changes in mean daily pad use (0.8 at 1 year; P = 1.000), in ICIQ score (5.0 at 3 years vs 5.2 at 1 year; P = 0.500), or in IQOL score (89.2 at 3 years vs 86.8 at 1 year; P = 0.500) were observed. Patients lost less urine based on 24‐h pad testing after nearly 3 years (14 g at 3 years vs 28 g at 1 year; P = 0.106). Subgroup analyses showed no significant differences in efficacy in patients who had previously received radiotherapy or in patients with mild preoperative incontinence. Between 1 and 3 years postoperatively, no complications were detected. Conclusions: The present study had the longest follow‐up for AdVanceXP to date and is the first to show a high efficacy even after a mean follow‐up of almost 3 years. The results indicate that late‐onset complications are rare after AdVanceXP implantation.